2021
DOI: 10.3390/cells10112818
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Accessibility and Transcriptomic Alterations in Murine Ovarian Granulosa Cells upon Deoxynivalenol Exposure

Abstract: Deoxynivalenol (DON) is a common environmental toxin that is secreted by fusarium fungi that frequently contaminates feedstuff and food. While the detrimental effects of DON on human and animal reproductive systems have been well recognized, the underlying mechanism remains poorly understood. Ovarian granulosa cells (GCs), which surround oocytes, are crucial for regulating oocyte development, mainly through the secretion of hormones such as estrogen and progesterone. Using an in vitro model of murine GCs, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The RNA in the porcine liver was prepared for RNA-seq analysis. The data were processed and analyzed according to the previous statements . Genes (adjusted P value < 0.05, |Log 2 -fold change| >1 between 2 samples) were defined as differentially expressed genes (DEGs) (DON versus vehicle, DON + NaBu versus DON).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA in the porcine liver was prepared for RNA-seq analysis. The data were processed and analyzed according to the previous statements . Genes (adjusted P value < 0.05, |Log 2 -fold change| >1 between 2 samples) were defined as differentially expressed genes (DEGs) (DON versus vehicle, DON + NaBu versus DON).…”
Section: Methodsmentioning
confidence: 99%
“…Mycotoxin is tightly linked with the transcriptional processes involved in NR-mediated regulation . Increasing evidence have shown that NRs exert cardinal roles in regulating DON-induced OS and inflammatory genes through the recruitment of histone modifiers. , Apart from mediating inflammatory processes through the activation of IL-8 and the suppression of IL-4 in T-reg, , NR4A2 (encodes the NURR1 protein) also inhibits the transcription of the OS gene. , Sodium butyrate (NaBu) is a short-chain fatty acid that increases the average daily weight gain of piglets, provides energy for intestinal epithelium, plays an immunomodulatory role, and also regulates lipid metabolism in the liver and intestine . Notably, as a vital ligand of NR and a natural HDAC inhibitor, NaBu could alleviate DON-induced OS and inflammation. , Moreover, NaBu exerts anti-inflammatory effects by increasing the H3K9ac profiles at promoter regions of the pro-inflammatory genes and enhancing NR PPARA activation. Therefore, we hypothesize NaBu resists DON-induced OS and the inflammatory response through histone acetylation recruited by NR4A2 .…”
Section: Introductionmentioning
confidence: 99%
“…Nlrp4f , PadI6 , Tcf21 (ECM/actin/microtubule organization), Zp2 (the transcriptional repressor in the circadian system that targets Cyp19a1 expression and inhibits estrogen synthesis ( Nr1d1 )) [ 92 ], and Nlrp14 (oocyte and spermatogenic marker) [ 93 ] were upregulated also after exposure to deoxynivalenol (DON). DON is an environmental toxin that frequently contaminates cereal crops and food and disrupts estrogen and progesterone secretion in murine granulosa cells [ 94 ]. Crabp2 , Crip1 , Dhcr4 , Fst, and Sfrp1 were also downregulated after exposure to DON.…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that one of the reasons why so few genes overlap may be histone modification. Fan, Ren ( Fan et al, 2021 ) also found fewer genes intersected when investigating the association between the specific chromatin-accessible regions and gene expression in murine ovarian GCs upon DON exposure. One potential mechanism is histone acetylation (acetyltransferases/deacetylases) and methylation (methyltransferases/demethylases) between histones and DNA regulating gene expression ( Bhaumik et al, 2007 ).…”
Section: Discussionmentioning
confidence: 96%